Analysis of Teachers' Creativity in SBDP Learning Class V SDN 24 Palu - Maggi, Desilia Pramesti Titania; Lagandesa, Yun Ratna; Aqil, Muhammad; Zulnuraini, Zulnuraini; Fasli, Muhammad (FKIP - Universitas Riau, 2025)
This study aims to analyze the creativity of teachers in learning SBDP (Arts, Culture and Crafts) at SDN 24 Palu. This study uses a type of qualitative research using observation, interview, and documentation data collection techniques. The result of this study is that grade V teachers of SDN 24 Palu from five indicators of teacher creativity, namely developing interesting and diverse activities, making learning aids, utilizing the environment, managing classrooms and learning resources and implementing learning processes and outcomes, including teachers in grade V of SDN 24 Palu meet the four indicators of teacher creativity. One of the indicators that is not achieved is utilizing the environment because teachers only do learning in the classroom and do not utilize learning resources from around the school or other environments. The cause of the non-implementation of these indicators in SBdP learning in this school is due to inadequate environmental conditions or school yards or it can be said that the school yard is not spacious so that if you want to do outdoor activities, the students' movement space is limited. So it can be concluded that grade V teachers of SDN 24 Palu are included in the Good category and show indicators of teacher creativity in SBdP learning.